Chapter Una tragedia cinquecentesca italo-spagnola: La Reyna Matilda di Giovan Domenico Bevilacqua - cremante, renzo (Studi e saggi, 2020)
The subject of the intervention, a curious example of Italian-Spanish translingualism of the late 16th Century, the tragedy La Reyna Matilda, written in Naples in Spanish by an Italian writer, Giovanni Domenico Bevilacqua, secretary of the Prince of Conca, Matteo di Capua, and preserved in a single, very rare Neapolitan edition of 1597. It necessarily precedes a brief overview of the other few previously printed works by the author, all in Italian, including the renown octave-rhyme translation of the De raptu Proserpinae by Claudiano. Set in the city of Tarragona at the time of Reconquista, the fabula ficta is characterized by the contamination of tragic plot and novelistic themes, the representation and exaltation of Spanish values and customs, with some reflections of contemporary Neapolitan reality, the pietistic and edifying motivations. Through detailed findings, both formal and intertextual, the analysis focuses, in particular, on the debts that the tragedy has, even before the contemporary Spanish developments of the genre, towards the 16th Century Italian tragic grammar, along the entire arc of its codification, from Trissino's Sofonisba to Tasso's Re Torrismondo.